2015
DOI: 10.1136/gutjnl-2014-309014
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-infiltrating neutrophils represent the main source of IL-23 in the colon of patients with IBD

Abstract: This study provides the first evidence of CXCR1(+)CXCR2(+)IL-23-producing neutrophils that infiltrate and accumulate in inflamed colon tissue of patients with IBD. Thus, this novel source of IL-23 may play a key role in disease progression and will be important to take into consideration in the development of future strategies to monitor, treat and prevent IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 56 publications
3
65
1
Order By: Relevance
“…For example, it was previously shown that, while Helicobacter pylori Neutrophil Activating Factor triggers the expression of IL‐23p19 mRNA by human neutrophils, Borrelia burgdorferi NapA, but not OspA, induces IL‐23 at both gene expression and protein level . In another study, both blood neutrophils and neutrophils infiltrating colon tissue of pediatric patients with inflammatory bowel disease were found to express IL‐23p19 (as revealed by immunohistochemistry and immunofluorescence), using an Ab detecting only the IL‐23p19 monomer, which is secreted by many cell types but is biologically inactive. More recently, human neutrophils (whose purity was not stated) were shown to express IL‐23 (presumably IL‐23p19) mRNA, as well as to produce very elevated levels of IL‐23 protein, when infected with Mycobacterium tuberculosis H37Rv or when incubated with either LPS or Pam3CSK4 (a TLR2 agonist) .…”
Section: Discussionmentioning
confidence: 97%
“…For example, it was previously shown that, while Helicobacter pylori Neutrophil Activating Factor triggers the expression of IL‐23p19 mRNA by human neutrophils, Borrelia burgdorferi NapA, but not OspA, induces IL‐23 at both gene expression and protein level . In another study, both blood neutrophils and neutrophils infiltrating colon tissue of pediatric patients with inflammatory bowel disease were found to express IL‐23p19 (as revealed by immunohistochemistry and immunofluorescence), using an Ab detecting only the IL‐23p19 monomer, which is secreted by many cell types but is biologically inactive. More recently, human neutrophils (whose purity was not stated) were shown to express IL‐23 (presumably IL‐23p19) mRNA, as well as to produce very elevated levels of IL‐23 protein, when infected with Mycobacterium tuberculosis H37Rv or when incubated with either LPS or Pam3CSK4 (a TLR2 agonist) .…”
Section: Discussionmentioning
confidence: 97%
“…A correlation between frequencies of neutrophils and endoscopic severity was reported in ulcerative colitis [4] and was proposed in Crohn's disease using quantification of fecal calprotectin or Indium-111 scanning [28,29]. However, apparently contradictory studies suggest that CD may result from a defect in neutrophil recruitment, and that recruited neutrophils are either dysfunctional or display proinflammatory functions [18,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Sources of IL23 include macrophages, dendritic cells, neutrophils, and epithelial cells 8,9,13,14 . Cells that produce IL17 (generally referring to IL17A, with 6 members in the family described) are also highly enriched in mucosal tissues 11 .…”
Section: Il23 and Th17 Cell Pathwaysmentioning
confidence: 99%